Effects of the physical form of diet on growth performance, ascites and sudden death syndrome incidences in broiler chickens - AZIZIAN, M.; SAKI, A.A. (Journal of the Hellenic Veterinary Medical Society, 2020)
This experiment was conducted to determine the effects of the diet physical form, Mash (M), Pellet (P) and Extruded (E) on the growth performance, carcass characteristics and metabolic disorders ascites (AS) and as well as sudden death syndrome (SDS) in the broiler chickens. In this respect, feed intake (FI), weight gain (WG) and mortality were recorded throughout the experiment and biochemical parameters, hematology and carcass characteristics were tested at 35 and 42 days of age respectively. The results showed that with the increase of the average daily weight gain (ADWG) (p<0.01), the relative breast weight to the carcass weight (p<0.05), better feed conversion ratio (p<0.01), the lower relative cecum weight and gizzard to the carcass weight (p<0.05) were observed by applying the E diet form, as compared with the other treatments. A significant increase in the average daily feed intake (ADFI) was also observed by using the P diet form (p<0.01). Hematological parameters including hemoglobin (Hb), hematocrit (HCT), urea, uric acid, triglyceride, the ratio of low-density lipoprotein to high-density lipoprotein (LDL/HDL), very low-density lipoprotein (VLDL), enzyme activities of aspartate aminotransferase(AST) and alanine aminotransferase (ALT) of the blood serum were lowered by applying the M treatment, as compared with the other treatments (p<0.05). The results indicated that the performance and carcass characteristics were improved by the E and P diet forms; also, with raising the hematology parameters in these treatments, the mortality of ascites and SDS was increased.